A Linearized Difference Scheme for the Kuramoto-Tsuzuki Equation (Journal of Computational Mathematics, 1996)
In this paper, a linearized three-level difference scheme is derived for the mixed boundary value problem of Kuramoto-Tsuzuki equation, which can be solved by double-sweep method. It is proved that the scheme is uniquely solvable and second order convergent in energy norm.